2007
DOI: 10.1016/j.immuni.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a Functional T Cell Receptor during T Lymphocyte Development Is Enforced by HEB and E2A Transcription Factors

Abstract: The T cell receptor (TCR) is required for positive selection and the subsequent transition from the CD4(+)CD8(+) double-positive (DP) to the CD4(+) or CD8(+) single-positive (SP) stage of alphabeta T cell development. The molecular mechanism that maintains DP fate prior to the acquisition of a functional TCR is not clear. We have shown here that the structurally and functionally related transcription factors HEB and E2A work together to maintain DP fate and to control the DP to SP transition. Simultaneous dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 38 publications
6
143
0
Order By: Relevance
“…However, our data are consistent with the low abundance of E2A and presumably also of HEB in CD4 cells (32)(33)(34)(35) and with the fact that Mi-2b deletion impairs CD4 expression in DP, but not CD4, cells (11). Furthermore, combined HEB/E2A deletion does not impair CD4 expression in the peripheral CD4 cells, whereas the expression in DP cells is apparently affected (36). Together these data suggest that CD4 expression in CD4 cells requires some unknown factors.…”
Section: Figsupporting
confidence: 88%
“…However, our data are consistent with the low abundance of E2A and presumably also of HEB in CD4 cells (32)(33)(34)(35) and with the fact that Mi-2b deletion impairs CD4 expression in DP, but not CD4, cells (11). Furthermore, combined HEB/E2A deletion does not impair CD4 expression in the peripheral CD4 cells, whereas the expression in DP cells is apparently affected (36). Together these data suggest that CD4 expression in CD4 cells requires some unknown factors.…”
Section: Figsupporting
confidence: 88%
“…In vitro reporter assays suggested that, among these, the 5 9 E box of the CD4-3 element is essential for enhancer activity. This E box was bound by HEB/E2A complexes in vitro, and DP thymocytes lacking HEB or both HEB and E2A had reduced Cd4 expression (11,12). In contrast, two E boxes, which are located in CD4-1 and at the 3 9 end of CD4-3, are not required for enhancer activity in vitro, and their functions have not been identified (9,10).…”
Section: Resultsmentioning
confidence: 97%
“…Many bHLH genes expressed during development and involved in the induction of cellular differentiation may be absent from this bHLH gene set. An example is the role that Tcfe2a (bHLHb21) has in thymic cell differentiation (Jones and Zhuang, 2007), but was absent from the bHLH gene set, Table 1. Therefore, further developmental analysis using the entire bHLH family is needed in the future.…”
Section: Discussionmentioning
confidence: 99%